DOMESTIC MARKET DEMAND IDENTIFICATION FOR SUSTAINABLE BAMBOO ECOTOURISM PRODUCT DEVELOPMENT STRATEGY IN SEMBALUN LAWANG - Lia Rosida; Syech Idrus; Sri Wahyuningsih; Lalu Yulendra; Si Luh Putu Damayanti; Distiya Azhari; Yusuf Martadinata (International Journal of Geotourism Science and Development, 2021)
Despite its applaudable economic benefits (Fleischer & Felsenstein 2000, Goodwin 2008), over-tourism could cause detrimental effects on environment and local cultures. Ecotourism as one of the fastest growing industries in the world (UNWTO, 2001; Self et al, 2010) that balances between economic opportunity as well as cultural and natural preservation should be pervasively applied in Indonesia with abundant natural and cultural competitiveness as the third largest biodiversity in the world after Brazil and Zaire (Janita, 2012). Previous studies revealed the needs to conduct research on responsible marketing and very limited studies investigate responsible product development for bamboo ecotourism concept. Hence, this quantitative study with 64 respondents (18-53 y-o) aims at examining Indonesian domestic market needs and trends as a basis to design responsible bamboo ecotourism products as a part of responsible marketing efforts in Sembalun Lawang, Lombok, Indonesia. This study was carried out through online questionnaire by attaching short-video and description about Sembalun Lawang bamboo forest attractions for ecotourism. The research result shows that 92% of respondents found the bamboo forest is attractive and suitable for ecotourism concept. Among 18 potential activities, the study shows top five desired bamboo ecotourism activities encompassing; picture taking at natural spots, nature walk, learning about local culture on bamboo usage, learning about types and benefits of bamboo plants, and enjoying surrounding fauna and flora. Since the study is confined to Indonesian domestic market research, further research should be carried out to examine international market research trend for responsible bamboo ecotourism development.